Information mining in patent filings on injectable antineoplastics as a contribution to Health Policy (Research, Society and Development, 2022)
Introduction: According to data from the United Nations, cancer is the second leading cause of death in the world. Currently, information management has been increasingly difficult due to the large amount of data to be managed. In general, the databases that store patent documents make it possible to read them in full, but do not allow the extraction and treatment of large amounts of data. In this sense, it is necessary to use management software. Objective: To identify, extract, process the data, organize, and make available, in the form of graphical interfaces, the technological information on injectable oncology described in the current patents. Methodology: Patents deposited between January 2002 and July 2022 were analyzed using the ORBIT Intelligence® platform. In the “Advanced Search” field, the “Title, Abstract” filters were applied and the search terms: “injectable AND cancer” were used. Results and Discussion: 115 patent families were identified. The USA stands out in the number of patent documents filed, presenting a total of 56 documents. Inventors Ivan Edward Hofman, Farber Michael, Franco Rodriguez Guillermo and Gutierro Aduriz Ibon were the most productive, each with 3 documents deposited. The institutions Bespoke Bioscience (USA), Immunocore Holdings (United Kingdom) and Mountain Valley MD Holding (Canada) stood out, each holding 3 documents. In the documents analyzed, the most recurrent technological domain went beyond the "pharmaceutical" technological domain, which obtained 109 documents and others such as chemical, biological, electrical, micro and nanotechnology. Final Considerations: The results obtained by mining the data extracted from patent documents proved to be efficient and, can be useful as an effective tool to analyze, compare and monitor research and innovation activities in injectable oncology.